2014
DOI: 10.1002/cncr.28912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex on the survival of patients with hepatocellular carcinoma: A Surveillance, Epidemiology, and End Results analysis

Abstract: BACKGROUND: Men are 4 to 8 times more likely to develop hepatocellular carcinoma (HCC) than women. Preclinical models have suggested a role for sex hormones in the development of HCC. In the current study, the authors investigated the impact of age, sex, race, and ethnicity on the survival of patients with HCC using the Surveillance, Epidemiology, and End Results (SEER) database. METHODS: Patients diagnosed with HCC from 1988 through 2010 were identified from the SEER registry. Hazard ratios (HR) for overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
105
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 59 publications
(91 reference statements)
17
105
1
Order By: Relevance
“…A retrospective study of 10,608 patients conducted by Norris Comprehensive Cancer Center demonstrated no gender-related difference in survival in Asian patients with HCC [20]. However, an autopsy study showed that a tumor thrombus was more common in female patients, and hormonal factors might play a role in neoplastic vascular invasion [21].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 10,608 patients conducted by Norris Comprehensive Cancer Center demonstrated no gender-related difference in survival in Asian patients with HCC [20]. However, an autopsy study showed that a tumor thrombus was more common in female patients, and hormonal factors might play a role in neoplastic vascular invasion [21].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD-related HCC may also occur in non-cirrhotic livers, but this seems to be more likely in men [104]. The sexual dimorphism in HCC is also maintained regarding prognosis, with women showing better survival rates [102, 105]. However, menopause seems to attenuate these advantages [102, 105].…”
Section: Epidemiology Of Nafldmentioning
confidence: 99%
“…For the gender difference in HCC, it has been reported that survival in HCC of women is better compared to men; however, the reason had not been clearly elucidated (19,20). According to previous research that implied the cause of the sex difference in survival with HCC, women were more closely followed-up compared to men in the detection of early-stage HCC among high-risk patients (19).…”
Section: Discussionmentioning
confidence: 99%